Fruit characterization of different avocado (Persea americana Mill.) genotypes in eastern mid-hills of Nepal - Poudel, Krishna; Shah, Manoj Kumar; Mandal, Jawahar Lal; Shrestha, Jiban (Journal of Agriculture and Natural Resources, 2018)
The total of thirteen different avocado (Persea americana Mill.) genotypes were collected for evaluating the fruit characteristics in the laboratory of Agricultural Research Station, Pakhribas during November 2017. The fully matured fruits from the farmer’s field at Patle, Dhankuta were collected. The criteria for selecting the genotypes were fruit weight, fruit length, fruit diameter, seed weight, pulp weight, pulp to fruit ratio and the seed weight percentage. The result suggests the potentiality of the genotypes PAKAV002 and PAKAV010 in most of the evaluated characters as compared to the tested genotypes. The genotypes PAKAV008 and PAKAV007 were disliked as they have 32.59% and 28.39% of seed weight to the total fruit weight. The genotypes PAKAV002 and PAKAV010 had the average fruit weight ranging (307.1 g and 346.8 g), maximum of pulp to fruit ratio 62.34% and 56.97%. Similarly, genotypes PAKAV010 (11.425%), PAKAV013 (11.96%) and PAKAV002 (14.47%) had low seed weight to the total fruit weight which is regarded important factor for avocado selection and evaluation. This result shows that the genotypes PAKAV002 and PAKAV010 should be further evaluated for fruit characteristics and the quality.